The Implementation of TED Talk Video (TTV) as a Media to Teach Listening for Al-Hikmah Students at CEFR Level B1 - Khoironi; Faishol Hadi (Journal of English Language Teaching and Islamic Integration, 2018)
The  major  goal  of  this  study  is  to  investigate  the implementation  of  TED  Talk  Video  (TTV)  as  a  media  for  teaching listening in the classroom and to explore the students’ response towards TTV in teaching listening. Listening skill, as one of the most important skills  in  English,  needs  excellent  media  as  a  great  support  to  teach students about it, and TTV is assumed to be fascinating media to teach it. The common problem faced by the teachers in teaching listening is that they lack of alternative media to be used to teach it. Conventional way  is  the  only  way  to  teach  them,  such  as  by  providing  the  audio sound  which  is  not  effective  to  teach  listening.  So,  this  research  is considered to be important as a means to explore the implementation of TED Talk video. This qualitative research method involved a class of STKIP Al-Hikmah  students  who rich B1 level of  English proficiency where  most  of  them  faced  the  similar  problems  in  learning  listening. The  data  were  gathered  through  interview,  observation,  and questionnaires. The data collected by the researcher revealed that TED Talk  Video  is  suitable  and  applicable  to be  implemented  for  students who are in B1 level of English proficiency. The data also proved that both  teacher  and  students  felt  more  comfortable  to  conduct  teaching-learning  process.  Most  students  said  that  TTV  gave  more  advantages than  the  disadvantages  related  to  their  listening  skill.  Thus,  it  can  be assumed that TTV is pertinent media to be used for teaching listening.